FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU SEKSUAL PADA REMAJA - Wilda Wahyuni Siregar; Dwi Handayani (JURNAL ILMIAH DHDT - KEBIDANAN, 2018)
Adolescent sexual and reproductive health has become a national problem at this time. Adolescent sexual behavior that leads to an increase in premarital sexual relations is triggered by dating activities. Adolescent sexual behavior will have negative effects such as pregnancy in adolescents, abortion, unwanted pregnancy, sexually transmitted diseases and HIV / AIDS. BKKBN data from Deli Serdang Regency in 2016 states that 15-20 of 9382 teenagers experience pregnancy at a young age due to early sexual behavior. The purpose of this study was to determine the factors that influence sexual behavior in adolescents in the District Lubuk Pakam in 2017. This type of research uses a cross sectional approach with the implementation time in February-May 2017. The population in this study were all adolescents in Lubuk Pakam District aged 15 -19 years totaling 9382 people and a total sample of 128 people. Data were obtained using questionnaires analyzed using multiple logistic regression. The results of the study showed that the sexual behavior of teenagers in the high risk category was 43.0%. Predispossing factors: adolescent knowledge of not good category as much as 53.9%, negative category attitude 54.7%, and low socio-economic category 57.8%. Enabling factors: source (media) information 56.3% of exposed categories. Reinforcing factors: the role of the closest person 57.8% in the role category, self control 59.4% in the uncontrolled category, and the lifestyle of 68.8% in the modern category. The results of statistical tests using SPSS found that predispossing, enabling factors and reinforcing factors had a significant relationship with adolescent sexual behavior. The most dominant variable on adolescent sexual behavior is attitude with p = 0.002. It is suggested to the local government to further enhance positive activities in adolescents in order to avoid the occurrence of deviant sexual behavior.